Intrinsic Iron Release Is Associated with Lower Mortality in Patients with Stable Coronary Artery Disease—First Report on the Prospective Relevance of Intrinsic Iron Release - Julia Ruhe; Christoph Waldeyer; Francisco Ojeda; Alev Altay; Renate B. Schnabel; Sarina Schäfer; Karl J Lackner; Stefan Blankenberg; Tanja Zeller; Mahir Karakas (Biomolecules, 2018)
Intrinsic iron release is discussed to have favorable effects in coronary artery disease (CAD). The aim of this study was to evaluate the prognostic relevance of intrinsic iron release in patients with CAD. Intrinsic iron release was based on a definition including hepcidin and soluble transferrin receptor (sTfR). In a cohort of 811 patients with angiographically documented CAD levels of hepcidin and sTfR were measured at baseline. Systemic body iron release was defined as low levels of hepcidin (<24 ng/mL) and high levels of sTfR (≥2 mg/L). A commercially available ELISA (DRG) was used for measurements of serum hepcidin. Serum sTfR was determined by using an automated immunoassay (). Cardiovascular mortality was the main outcome measure. The criteria of intrinsic iron release were fulfilled in 32.6% of all patients. Significantly lower cardiovascular mortality rates were observed in CAD patients with systemic iron release. After adjustment for body mass index, smoking status, hypertension, diabetes, dyslipidemia, sex, and age, the hazard ratio for future cardiovascular death was 0.41. After an additional adjustment for surrogates of the size of myocardial necrosis (troponin I), anemia (hemoglobin), and cardiac function and heart failure severity (N-terminal pro B-type natriuretic peptide), this association did not change (Hazard ratio 0.37 (95% confidence interval 0.14–0.99), p = 0.047). In conclusion, significantly lower cardiovascular mortality rates were observed in CAD patients with intrinsic iron release shown during follow-up.